Educação especial no Brasil: os primeiros passos e seus princípios norteadores - Carvalho Amaral, Bruna Carla de (Faculdade de Filosofia e Ciências, 2019)
The present work seeks to relate the historical context and the ideological influences that surrounded the creation of the first experiences in formal special education in Brazil. To do so, we used the survey carried out by Gilberta Jannuzzi in his work A Educação do deficiente no Brasil: dos primórdios ao início do século XXI, with emphasis on the period of the First Republic. In the analyzed context, from a bibliographical review, it was possible to verify that this scenario was strongly influenced by liberal ideas, scientism, escolanovismo, hygienism, eugenism and scientific pedagogy. There was a significant influence of medical power regarding the determination of normality, health and insanity patterns and the internal organization of schools and the design of bases for special education. Recebido: 01/04/2019 Aceito: 01/05/2019